The impact of blended learning on knowledge, skills and satisfaction in mathematics: a study in Indonesian universities - Khoerul Umam; Mohd Isha Awang; Bunyamin; Ervin Azhar; Ishaq Nuriadin (Cogent Education)
Blended learning, a method that combines face-to-face and online instruction, has had a significant impact on higher education due to the rapid advancement of information and communication technology. This study analysed the effect of blended learning on students’ knowledge, skills and learning satisfaction in mathematics. This study focuses on mathematics learning specifically at the university level. A survey was conducted on 304 Indonesian university students engaged in blended learning for mathematics. Using the Structural Equation Model - Partial Least Squares (SEM-PLS) method, the analysis revealed that blended learning significantly improves students’ knowledge and skills, which in turn positively impacts their learning satisfaction. These results were statistically significant. This study offers valuable insights for optimising curriculum design in higher education to enhance the implementation of blended learning and improve the quality of mathematics learning, particularly by highlighting effective teaching methods within this modality.